Effects of Zoledronate on Cancer, Cardiac Events, and Mortality in Osteopenic Older Women. (11th October 2019) - Reid, Ian R; Horne, Anne M; Mihov, Borislav; Stewart, Angela; Garratt, Elizabeth; Bastin, Sonja; Gamble, Gregory D
ABSTRACT: We recently showed that zoledronate prevented fractures in older women with osteopenia (hip T ‐scores between −1.0 and −2.5). In addition to fewer fractures, this study also suggested that women randomized to zoledronate had fewer vascular events, a lower incidence of cancer, and a trend to lower mortality. The present analysis provides a more detailed presentation of the adverse event data from that study, a 6‐year, double‐blind trial of 2000 women aged >65 years recruited using electoral rolls. They were randomly assigned to receive four infusions of either zoledronate 5 mg or normal saline at 18‐month intervals. Supplements of vitamin D, but not calcium, were provided. There were 1017 serious adverse events in 443 participants in the placebo group, and 820 events in 400 participants in those randomized to zoledronate (relative risk = 0.90; 95% CI, 0.81 to 1.00). These events included fractures resulting in hospital admission. Myocardial infarction occurred in 39 women (43 events) in the placebo group and in 24 women (25 events) in the zoledronate group (hazard ratio 0.60 [95% CI, 0.36 to 1.00]; rate ratio 0.58 [95% CI, 0.35 to 0.94]). For a prespecified composite cardiovascular endpoint (sudden death, myocardial infarction, coronary artery revascularization, or stroke) 69 women had 98 events in the placebo group, and 53 women had 71 events in the zoledronate group (hazard ratio 0.76 [95% CI, 0.53 to 1.08]; rate ratio 0.72 [95% CI, 0.53 to 0.98]). Total cancers were significantly reduced with zoledronate (hazard ratio 0.67 [95% CI, 0.51 to 0.89]; rate ratio 0.68 [95% CI, 0.52 to 0.89]), and this was significant for both breast cancers and for non‐breast cancers. Eleven women had recurrent or second breast cancers during the study, all in the placebo group. The hazard ratio for death was 0.65 (95% CI, 0.40 to 1.06; p = 0.08), and 0.51 (95% CI, 0.30 to 0.87) in those without incident fragility fracture. These apparent beneficial effects justify further appropriately powered trials of zoledronate with these nonskeletal conditions as primary endpoints. © 2019 American Society for Bone and Mineral Research.